2014
DOI: 10.1111/famp.12088
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Solutions: Gender Differences in Relationship and Parenting Challenges Among Low‐Income, Young Parents

Abstract: The need for parenting and relationship strengthening programs is important among low-income minority parents where the burden of relational and parental stressors contributes to relationship dissolution. We examine these stressors among young parents. Data were collected from four focus groups (N = 35) with young parents. Data were audio-recorded and transcribed. Inductive coding was used to generate themes and codes, and analysis was completed using NVivo. Relationship and parenting challenges, values, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…Common stressors for expecting young fathers include limited finances, unemployment, health of the mother and baby, parenting, and maintaining a relationship with the expecting mother (Elster and Panzarine 1983). In a previous study, we found mirroring concerns among young parenting fathers from racially diverse backgrounds (Albritton et al 2014). …”
Section: Mental Health and Parenting At A Young Agesupporting
confidence: 63%
See 1 more Smart Citation
“…Common stressors for expecting young fathers include limited finances, unemployment, health of the mother and baby, parenting, and maintaining a relationship with the expecting mother (Elster and Panzarine 1983). In a previous study, we found mirroring concerns among young parenting fathers from racially diverse backgrounds (Albritton et al 2014). …”
Section: Mental Health and Parenting At A Young Agesupporting
confidence: 63%
“…Given that young parents may experience stressors such as pregnancy concerns, adjustment to parenting, relationship strain and financial hardship (Albritton et al 2014; Kershaw et al 2013), it is essential that women and men seek mental health services and other supports as needed. As a couple, young parents are navigating complex familial and partner relationships, and it is important to understand factors that influence their use of mental health services and if partners influence utilization.…”
Section: Mental Health and Parenting At A Young Agementioning
confidence: 99%
“…In a recent study, researchers conducted focus groups with 35 low‐income, young parents asking about parenting and their relationships (Albritton et al ). Findings supported several differences between mothers and fathers.…”
Section: Gender Role Narratives and Parentingmentioning
confidence: 99%
“…Women may feel responsible for the nurturance and emotional wellbeing of their families (Albritton et al 2014;Hart 1996;Walters 1988), and there is a tendency for mothers to be blamed when things go wrong in the family system (Walters 1988). Meanwhile, men describe stress associated with feeling financially responsible for their families (Albritton et al 2014) and are more likely to be in charge of disciplining their children (McKee et al 2007;Walters 1988). Indeed, scholars suggest 'the stereotypic gender structure perpetuates male dominance in broader society, replicates the unequal gendered division of labour, and can leave men outside motherchild relationships and less emotionally connected with their children' (Matta & Knudson-Martin 2006;p.…”
Section: Gender Role Narratives and Parentingmentioning
confidence: 99%
See 1 more Smart Citation